2015
DOI: 10.2174/1874306401509010015
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Adults with Cystic Fibrosis Receiving Intravenous Antibiotics in Hospital and in the Community§

Abstract: Introduction : Intravenous antibiotic therapy (IVAT) for CF acute pulmonary exacerbations (APE) can be delivered in hospital or in the community. This study aimed to compare physical activity in CF patients receiving hospital and community-delivered IVAT, as well as other health outcomes.Materials and Methods : This was a non-randomised parallel group prospective observational study. Hospitalised and community-treated CF adults receiving IVAT for APE were asked to wear ActiGraph® activity monitors, complete th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Patients with > 2 exacerbations in the previous year spent less time in activity of mild intensity (> 3 METS) than patients with < 2 exacerbations (P 0.01). When accounting for confounding factors, physical activity was not related to exacerbation frequency in the previous year [63] Khiroya et al compared physical activity in CF patients receiving intravenous antibiotics for pulmonary infection in 22 inpatients and 23 outpatients during a 2 week treatment course. They found similar activity levels in the inpatient and outpatient treated groups, both being sedentary [64].…”
Section: Exacerbationsmentioning
confidence: 99%
“…Patients with > 2 exacerbations in the previous year spent less time in activity of mild intensity (> 3 METS) than patients with < 2 exacerbations (P 0.01). When accounting for confounding factors, physical activity was not related to exacerbation frequency in the previous year [63] Khiroya et al compared physical activity in CF patients receiving intravenous antibiotics for pulmonary infection in 22 inpatients and 23 outpatients during a 2 week treatment course. They found similar activity levels in the inpatient and outpatient treated groups, both being sedentary [64].…”
Section: Exacerbationsmentioning
confidence: 99%
“…In adult CF patients, work and transport-related activities are obvious reasons for reduced PA in everyday life compared with healthier and younger people [ 36 ]. Furthermore, with progress of the lung disease by age a higher need for intravenous therapies during pulmonary exacerbations is associated with reduced PA and increased sedentary time [ 37 ]. In our cross-sectional study, we found that a decrease of PA occurs during adolescence and young adulthood—which has been shown before by Britto et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has been shown to improve sputum clearance and lung function [41,42]. Patients who have been hospitalized with acute pulmonary exacerbations show a reduction in activity [43]. In parallel to this, adults who have had two or more exacerbations in the preceding year have lower activity levels, possibly due to their more advanced respiratory disease [44].…”
Section: Activity Monitoringmentioning
confidence: 99%